Definition of Tribal claim - حسوني, احمد; عودة, جليلة غضبان (Journal of Legal Sciences, 2019)
The tribunal is a new term in Iraqi law, where several projects including the law of the protection of Iraqi doctors No.26 of 2013 and before adopted the decision of the Board of Directors of the Revolution Decree No.2 and 7/4/1997, but the law maker did not show the most talented claims but also described them to the organization of the ratios and blood. As the regulations were organized by the civil and criminal court of 1918 during the British accupation of Iraqi, where the council of the senate and the specialists (DS) and the disputes of the disputes between the members of the clans and so the law shall be repeatedly working for the customary title and a law and is a law of the law and others crisis.